Temperature Distribution Monitoring on Blood Bank Chamber Using Android Application on Mobile Phone - Dianti Mayasari; Syaifuddin Syaifudin; Dyah Titisari; Triwiyanto Triwiyanto (Jurusan Teknik Elektromedik, POLTEKKES KEMENKES Surabaya, Indonesia, 2023)
Blood cold chain is a mandatory requirement of blood donation procedures to protect blood from bacterial contamination and to extend the shelf life of blood. Blood bank as a storage medium for blood bags requires a temperature between 2℃-6℃ on average. However, in general, blood banks only have 1 cold temperature distribution point, which is feared that the spread of cold temperatures in the compartment will be different at each point. For this reason, the researcher intended to design a blood bank temperature distribution monitoring device consisting of 7 measurement points. In this case, temperature sensor readings at each point are displayed wirelessly to smartphone devices using the Blynk platform and are also on a 3.5-inch TFT screen. The measurement data were then stored on the SD card memory so that the level of temperature fluctuations in the blood bank compartment can be analyzed during use. The module was also equipped with an alarm warning on the module and the Blynk application if the temperature is out of the normal temperature range (2℃-6℃). Before being used for measuring temperature distribution, the device made was compared with the standard Fluke DPM4 tester, in which the highest error obtained was 2.08% at T1, 1.58% at T2, -2.73% at T3, 1,61% at T4, -1.07% at T5, -0.06% at T6, and -2.32% at T7. After being compared with standard equipment, the device was used to measure the temperature spread in the Kirsch brand blood bank and the average temperature obtained was 3.56℃ at T1, 3.58℃ at T2, 3.73℃ at T3, 3.57℃ at T4, 3.67℃ at T5, 3.63℃ at T6, and 3.72℃ at T7. Based on the analysis results, the blood bank monitoring device can be used to measure the temperature spread in the blood bank compartment at 7 measurement points. Furthermore, temperature readings can be monitored wirelessly and remotely. It is hoped that this research can further help laboratory personnel at the Blood Transfusion Unit to monitor and evaluate the level of temperature spread in the blood bank compartment and prevent early damage to blood components.